2020
DOI: 10.1186/s12913-020-5021-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost of inappropriate antimicrobial use for upper respiratory infection in Japan

Abstract: Background: Antibiotics are often prescribed inappropriately to patients with upper respiratory infection (URI) in ambulatory care settings; however, the economic burden of such prescription has not been quantitatively assessed. Here, we aimed to evaluate the additional cost of antimicrobial prescription for URI at the population level in Japan. Methods:We conducted a retrospective observational survey using longitudinal claims data between 2013 and 2016 obtained from JMDC Claims Database, which contains data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The cohort included 2 804 245 eligible children (52% male; median [IQR] age,[8][9][10][11][12] years). Overall, 31% to 36% received inappropriate antibiotics for bacterial infections and 4% to 70% for viral infections.…”
Section: Resultsmentioning
confidence: 99%
“…The cohort included 2 804 245 eligible children (52% male; median [IQR] age,[8][9][10][11][12] years). Overall, 31% to 36% received inappropriate antibiotics for bacterial infections and 4% to 70% for viral infections.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, prescribing trends may have changed since March 2016, when the official guidelines were issued. In fact, Tsuzuki et al reported that the annual additional cost of inappropriate antibiotic prescription for upper respiratory tract infections decreased from 2013 to 2016 17 . Career-pressure may higher in elderly working age population according to the social status; However, our data did not have the status for career.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the sales of cephalosporins and the sum of all classes of antibiotics decreased gradually during the study period. Similarly, antibiotic use decreased during the same period [ 42 , 43 ]. The improved penicillin susceptibility rate of S .…”
Section: Discussionmentioning
confidence: 99%